Le coq médiéval - Michel Pastoureau (Revue d'ethnoécologie)
The medieval speech on the cock, inherited partly from Latin authors, is spread through bestiaries. Its ambivalent symbolism oscillates between, on one side, its generosity and courage, on the other one, its loftiness and its lustful character. An attribute of Gaul, then of the kings of France from the reign of Charles VII (1422-1461), the cock represents the Nation from the reign of Louis XIV, and its image is evoked then regularly in every conflict. During both world wars, it is the emblem of France battling against the invader.